An evaluation of public participation information for land use decisions: public comment, surveys, and participatory mapping. Issue 2 (1st February 2020) - Brown, Greg; Eckold, Henry
ABSTRACT: Public participation in the form of public meetings and written submissions has been criticised as a democratic ritual that fails to give citizens a real voice in government decisions. Participatory mapping and community surveys are alternative public participation (PP) methods that can augment legally required processes for land use planning. To date, there has been little evaluation research comparing the information content generated by required PP processes and alternative PP sources with respect to local land use decisions. Using multiple development projects from a case study community, we analysed and compared information generated from three different sources of public participation: (1) formal public comment (written submissions), (2) responses to community survey questions, and (3) land use preferences generated from participatory mapping. We found public comment strongly supported development while results from survey questions and participatory mapping methods revealed community ambivalence. The differences in public opinion are attributed to two key factors: the representativeness of participants in the PP process and the specific methods used for measuring public opinion. Community surveys and participatory mapping generated more accurate and representative community information compared to the formal PP process which was characterised by lower participation and vulnerability to special interest manipulation. For local government decision makers, the political risk of broadening PP information appears high relative to the risk of inaccurately assessing public opinion thus limiting adoption of alternative PP methods such as participatory mapping.